2012
DOI: 10.1093/jxb/ers250
|View full text |Cite
|
Sign up to set email alerts
|

Cellular ion homeostasis: emerging roles of intracellular NHX Na+/H+ antiporters in plant growth and development

Abstract: Recent evidence highlights novel roles for intracellular Na(+)/H(+) antiporters (NHXs) in plants. The availability of knockouts and overexpressors of specific NHX isoforms has provided compelling genetic evidence to support earlier physiological and biochemical data which suggested the involvement of NHX antiporters in ion and pH regulation. Most plants sequenced to date contain multiple NHX members and, based on their sequence identity and localization, can be grouped into three distinct functional classes: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
188
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(204 citation statements)
references
References 115 publications
8
188
1
7
Order By: Relevance
“…As found previously, the EE/TGN fraction of VSR organelles was more acidic than the PVC ( Figure 8E; Tukey test, P value < 0.001). Recently, it was proposed that endosomal NHX antiporters are also necessary for regulating endosomal pH and required for proper vacuolar sorting (Bassil et al, 2011b(Bassil et al, , 2012. Consequently, we coexpressed pH-VSR with NHX5-RFP and found that 23% of pH-VSR colocalized with NHX5-RFP ( Figures 8C and 8D).…”
Section: The Ph In the Lumen Of The Tgn Is More Acidic Than That In Tmentioning
confidence: 79%
See 1 more Smart Citation
“…As found previously, the EE/TGN fraction of VSR organelles was more acidic than the PVC ( Figure 8E; Tukey test, P value < 0.001). Recently, it was proposed that endosomal NHX antiporters are also necessary for regulating endosomal pH and required for proper vacuolar sorting (Bassil et al, 2011b(Bassil et al, , 2012. Consequently, we coexpressed pH-VSR with NHX5-RFP and found that 23% of pH-VSR colocalized with NHX5-RFP ( Figures 8C and 8D).…”
Section: The Ph In the Lumen Of The Tgn Is More Acidic Than That In Tmentioning
confidence: 79%
“…Monensin, bafilomycin A, and concanamycin A induce massive changes in Golgi morphology with an increase of saccules and an accumulation of vesicles at the trans face of the Golgi (Dettmer et al, 2006;Scheuring et al, 2011). Recently, endosomal NHX-type Na + /H + antiporters have been proposed to play a role in maintaining pH homeostasis (Bassil et al, 2011a(Bassil et al, , 2012, as other cation/H + exchangers do (reviewed in Chanroj et al, 2012). In mammalian cells, NHX-type antiporters have been suggested to function as proton leaks to counterbalance luminal acidification generated by V-ATPases (Demaurex, 2002;Orlowski and Grinstein, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the major cause of damage is the toxic effect of excessive Na + and K + ions in the cytoplasm (Golldack et al, 2014). Research has shown that a protein called Na + (K + )/H + antiporter (NHX) plays important roles in maintaining the proper ion homeostasis in the cytoplasm (Mahajan and Tuteja, 2005;Bassil et al, 2012 Skou, 1957), while the first plant homolog was found in barley in 1976 (Ratner and Jacoby, 1976). Since then, Na…”
Section: Introductionmentioning
confidence: 99%
“…Plant cells employ primary active transport, mediated by H -ATPase, and secondary transport mediated by channels and co-transporters in order to maintain high concentrations of K and low concentrations of Na in the cytosol. The overall sub cellular compartmentation of Na into the vacuole and other organelles, such as mitochondria and plastids also lowers Na concentration in the cytoplasm and at the same time contributes to osmotic adjustment in order to maintain water uptake under salt conditions and the AtNHX family of Na /H antiporters which localized in the tonoplast membrane here play an important role in Na compartmentation using the H gradient as a driving force across the membrane under salinity stress (Blumwald, 2000;Bassil et al, 2012). The first functionally-characterized member of this gene family, AtNHX1, contributes to Na and monovalent cation sequestration in plant vacuoles.…”
Section: Introductionmentioning
confidence: 99%